2011
DOI: 10.3390/su3091593
|View full text |Cite
|
Sign up to set email alerts
|

Do Respondents’ Perceptions of the Status Quo Matter in Non-Market Valuation with Choice Experiments? An Application to New Zealand Freshwater Streams

Abstract: Many issues relating to the sustainability of environmental resource use are informed by environmental valuation studies with stated preference surveys. Within these, researchers often provide descriptions of status quo conditions which may differ from those perceived by respondents. Ignoring this difference in utility baselines may affect the magnitude of estimated utility changes and hence bias benefit estimates of proposed environmental policies. We investigate this issue using data from a choice experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 49 publications
2
27
1
2
Order By: Relevance
“…This result contradicts the findings reported by Marsh et al (2011), which is one of the few papers that have tested the influence of scenario definition on SQE. The results of their DCE application suggest that participants who referred to their own SQ description had a higher preference towards the SQ, whereas participants individuals facing a predefined SQ tended to prefer the improvements proposed by the analysts.…”
Section: Discussioncontrasting
confidence: 99%
“…This result contradicts the findings reported by Marsh et al (2011), which is one of the few papers that have tested the influence of scenario definition on SQE. The results of their DCE application suggest that participants who referred to their own SQ description had a higher preference towards the SQ, whereas participants individuals facing a predefined SQ tended to prefer the improvements proposed by the analysts.…”
Section: Discussioncontrasting
confidence: 99%
“…Better communication of how algal increases are linked to reef degradation may be key in garnering public support for efforts such as the removal of algae from reefs, the reduction in nutrient pollution helping to drive increases (Smith et al, 2008), or the protection of herbivorous fish that maintain low levels of algae and facilitate coral recovery (Bellwood et al, 2004;Jackson et al, 2014). Our results demonstrate that shifting baselines can impact WTP, and build on previous work showing the importance of accounting for perceptions and subjective status-quo beliefs when eliciting WTP for ecosystem restoration (Meyerhoff and Liebe, 2009;Domínguez-Torreiro and Soliño, 2011;Marsh et al, 2011;Kataria et al, 2012;Artell et al, 2013). These studies also provide evidence that loss aversion can influence WTP (Neuman and Neuman, 2007;Bateman et al, 2009;EspinosaGoded et al, 2010;Masiero and Hensher, 2010), which may also be a possible mechanism to help explain our results.…”
Section: Discussionsupporting
confidence: 86%
“…Our results provide empirical evidence that shifting baselines, or failure to perceive past change, affect support for conservation and complement work that shows that perceptions of the current environment or the "status-quo" impact WTP (Meyerhoff and Liebe, 2009;Domínguez-Torreiro and Soliño, 2011;Marsh et al, 2011;Kataria et al, 2012;Artell et al, 2013). Specifically, we find that those who perceive more change in coral reef ecosystems are willing to pay more to protect them.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…They made use of property values or willingness to pay (WTP)/willingness to accept (WTA) of the public [59][60][61]. For example, Ansolabehere and Konisky [51] measured the public attitude towards nuclear power construction, and found that most Americans oppose having nuclear power plants in their neighborhood.…”
Section: Methods Of Testing the Nimby Syndromementioning
confidence: 99%